2006
DOI: 10.1007/s00535-006-1773-6
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for functional gastrointestinal disorders

Abstract: Functional gastrointestinal (GI) symptoms are common in the general population. Especially, motor dysfunction of the GI tract and visceral hypersensitivity are important. Acupuncture has been used to treat GI symptoms in China for thousands of years. It is conceivable that acupuncture may be effective in patients with functional GI disorders because it has been shown to alter acid secretion, GI motility, and visceral pain. Acupuncture at the lower limbs (ST-36) causes muscle contractions via the somatoparasymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(148 citation statements)
references
References 89 publications
6
139
0
3
Order By: Relevance
“…29 30 32 45 46 In human adults [47][48][49] and children 50 acupuncture had a benefi cial effect on visceral symptoms like nausea. Acupuncture increased bowel movement in children, 51 altered gastric motility 52 and affected gastric emptying in adults with motility disorders 53 but caused no effect on gastric motility in healthy individuals. 54 Manual acupuncture applied to LI4 induced an increase in the sympathetic and parasympathetic nervous systems in 12 healthy individuals.…”
Section: Possible Mechanisms and Explanationsmentioning
confidence: 98%
“…29 30 32 45 46 In human adults [47][48][49] and children 50 acupuncture had a benefi cial effect on visceral symptoms like nausea. Acupuncture increased bowel movement in children, 51 altered gastric motility 52 and affected gastric emptying in adults with motility disorders 53 but caused no effect on gastric motility in healthy individuals. 54 Manual acupuncture applied to LI4 induced an increase in the sympathetic and parasympathetic nervous systems in 12 healthy individuals.…”
Section: Possible Mechanisms and Explanationsmentioning
confidence: 98%
“…Acupuncture point ST36 is located in the proximal part of the anterior tibia muscle and is the acupuncture point considered for ailments of gastro-intestinal nature in traditional Chinese medicine (Deadman, Al-Khafaji, and Baker 2008). A postulated neurophysiologic mechanism explains a beneficial effect on gut dysmotility by way of the parasympathetic vagal reflexes, as well as a centrally opioid-mediated pain inhibitory pathway (Takahashi 2006).…”
Section: Acupuncturementioning
confidence: 99%
“…Acupuncture has been used for treating various GI diseases, including gastroparesis, functional dyspepsia (FD), irritable bowel syndrome (IBS), constipation and diarrhea [24] . Recent study showed that TENS applied to the acupuncture points (transcutaneous-EA; TEA) at the hands and lower legs improves GI symptoms in patients with FD [25] .…”
Section: Anti-stress Effects Of Somatosensory Stimulation 2-1 Effectmentioning
confidence: 99%